Unsolvable problems of justice and artificial intelligence - Mišić Marica (Glasnik Advokatske komore Vojvodine)
The history of philosophical (and legal-philosophical) thought shows that justice, as a principle, cannot be defined substantively, i.e., there is broad agreement that justice is something to strive for, but that, on the other hand, justice as a supreme or absolute principle cannot be substantively described. A middle way born from the relativity and changeability of the content of justice and its absoluteness as form is the concept of procedural justice or the inner morality of law, mainly the procedural requirements that a regulation must satisfy in order to be valid as law. Lawyers who, as Kant and many authors following him often apostrophize, have not yet found their own concept of law, now face new challenges posed by the development of modern technology and the use of artificial intelligence in various areas, as well as in certain domains of law. From dilemmas about the ethics and legal regulation of artificial intelligence to questions concerning the use of artificial intelligence in the process of creating, interpreting, and applying the law, solutions to the challenges that are the task of contemporary scientific thought and ethical and legal practice may shape the future of law. The paper will, inter alia, explore the possibility of realizing justice in the context of the use of artificial intelligence in the process of creating, interpreting, and applying the law, taking into account the thesis that iuspositivist conceptions of justice are insufficient for explaining and realizing justice.